Psychometric properties of the Adolescents’Academic Motivation Scale (AAMS) in a representative sample of Dominican Republic high school students - Reyes, Betty; Fernández, Irene; Pérez-Belmonte, Sergio; de los Santos, Saturnino; Tomás, José M.; Galiana, Laura (Anales de Psicología / Annals of Psychology, 2022)
Within the growing body of research that has focused on academic success, academic motivation has gathered considerable attention. The aim of this this research is to present the first validation of the Adolescents’ Academic Motivation Scale (AAMS). Total sample was composed by 1712 students of secondary education from two districts in the Dominican Republic. The main measurement outcome was the AAMS. Results from the CFA were satisfactory: χ2(5) = 57.73, p < .001; CFI = .970; RMSEA = .079 [.061, .097], and SRMR = .024. IRT analyses favored the two-parameter logistic model, indicating that items were not equally discriminant. Structural Equation Model with latent variables in which academic motivation was a significant predictor of grades resulted in excellent fit: χ2(53) = 182.76, p < .001; CFI = .980; RMSEA = .038 90% CI [.032, .044], and SRMR = .025. In sum, this work presents an exhaustive psychometric analysis of the AAMS in a representative sample of high school Dominican students.